Assessment of serum interleukin-8 as a sensitive serological marker in monitoring the therapeutic effect of levamisole in recurrent aphthous ulcers: A randomized control study - Prashant Gupta; L Ashok; Shantala R Naik (Wolters Kluwer Medknow Publications, 2014)
Aim: The study was designed to evaluate the serum interleukin-8 (IL-8) levels in patients with recurrent aphthous ulcer (RAU) and monitor the immunomodulation and altered IL-8 levels by levamisole before therapy and after levamisole therapy. Materials and Methods: This study was carried as a randomized case-control study involving a study group of 30 patients diagnosed as RAUs and given levamisole (vermisole 150 mg, od for 1 st 3 days of 3 weeks in a month and for 3 months with a gap of 1 week) and these patients were recalled after 3 months and were subjected for estimation of serum IL-8 levels. Control group had 20 age and sex matched individuals with no systemic illness and were not given any levamisole. Good compliance was reported at the end of the study. Results: Mild gastric irritation was reported and when severe it was managed by H1 blocker. Patients were reviewed after 3 months. The follow-up data at each visit with respect to each other and to base-line values was calibrated using a Students t-test. Highly significant comparisons were obtained in the serum IL-8 between study and control groups before the onset of levamisole (t = 6.53, P ≤ 0.001). IL-8 levels reduced by 72% after levamisole was instituted in RAU patients and comparison was highly significant for before and after levamisole onset (t = 5.54, P ≤ 0.001). Conclusion: This study points to the effectiveness of levamisole as an effective adjunct therapy in the routine management of RAU.